EKSPLORASI FAKTOR PENDUKUNG DAN FAKTOR PENGHAMBAT DALAM MELAKUKAN PROGRAM MANAJEMEN BERAT BADAN PADA MAHASISWA DENGAN OBESITAS DI UPN VETERAN JAKARTA STUDI KUALITATIF - Angelia Joselin, (2023)
This research explores the supportive and inhibiting factors in weight management programs among obese college students using a qualitative descriptive method and the Theory of Planned Behaviour as the analytical guide. Ten students from UPN Veteran Jakarta were the main informants, interviewed in-depth, supported by five additional supporting informants. The findings reveal that better attitudes and intentions are observed when the program aligns with daily habits but hindered by an unhealthy food environment. Weight loss efforts are perceived to align with values such as health and body aesthetics. Challenges arise when the surrounding environment does not support these efforts. The informants face an internal locus of control but struggle with controlling their eating desires and facing social pressures. The main obstacles stem from the discrepancy between the norms and control beliefs of teenagers and their environment, including peers and parents. Therefore, obesity prevention programs should involve the entire environment rather than solely focusing on teenagers.